Dietary Supplements and Military Operations: Caution is Advised. Issue 1 (1st March 2010) - Boos, Christopher; White, SH; Bland, SA; McAllister, PD
Abstract : We describe the case of a 32-year-old soldier who presented with acute organic psychosis during an operational tour to Iraq. This was precipitated by excessive consumption of caffeine coupled with additional use of oral nutritional stimulants. Her biochemical profile was compounded by the additional use of exogenous creatine. We present a brief overview of the issue of exercise supplementation and highlight some of the potential problems and clinical issues surrounding their use. This has important implications for both serving soldiers and the wider medical community.